1224 Effect of Distal Brachioradialis Release During Open Reduction and Internal Fixation of Distal Radius Fractures. (12th October 2021) - Hafez, A; Shaat, A; Zain, M; Sajid, M A; Butt, A
Abstract: Aim: The study aim is to determine the impact of the brachioradialis release during the open reduction and internal fixation of distal radius fractures using a volar approach Method: Total of 40 patients was treated with Open reduction and internal fixation of intra articular distal radius fractures. Distal release of Brachioradialis was performed to 19 patients, while 21 patients had no release of BR during surgery. Radiological parameters including Radial height, Inclination and volar tilt were measured 1 month post-operatively, while functional outcomes assessed with modified mayo wrist scores and Quick-dash scores Results: There is no significant difference between age, gender and pre-operative conditions indicating that both the groups (BR release and without BR release) have similar demographic characteristics. Pre-operatively both groups had disturbed values for radial height, inclination, and volar tilt. Postoperatively, the mean of both groups was closer to normal ranges for radial inclination and volar tilt; however, radial height was the least adequately restored radiological parameter for both study group (11.54 ± 1.35 for BR group versus 10.21 ± 2.29 for Non-BR group). Pain, functional status, and grip strength had similar values in both groups whereas BR group showed higher ROM and DASH scores with P values of 0.048 and 0.025 respectively. Conclusions: Brachioradialis release enhances the reduction and operative fixation, restoring the necessary radiological and subsequent functional parameters in distal radius fractures with reported no complications.